2014
DOI: 10.1038/mt.2014.61
|View full text |Cite
|
Sign up to set email alerts
|

Human Podoplanin-positive Monocytes and Platelets Enhance Lymphangiogenesis Through the Activation of the Podoplanin/CLEC-2 Axis

Abstract: Emerging studies suggested that murine podoplanin-positive monocytes (PPMs) are involved in lymphangiogenesis. The goal of this study was to demonstrate the therapeutic lymphangiogenesis of human PPMs by the interaction with platelets. Aggregation culture of human peripheral blood mononuclear cells (PBMCs) resulted in cellular aggregates termed hematospheres. During 5-day culture, PPMs expanded exponentially and expressed several lymphatic endothelial cell-specific markers including vascular endothelial growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…Consistent with the monocytic origin, human LECP were successfully differentiated in vitro using monocytes from peripheral [27,32,33] or umbilical cord [24,54] blood and treatment with a VEGF-A/VEGF-C cocktail. Here, we provide evidence that mouse and human myeloid-monocytic cells can undergo similar pro-lymphatic reprogramming upon activation of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the monocytic origin, human LECP were successfully differentiated in vitro using monocytes from peripheral [27,32,33] or umbilical cord [24,54] blood and treatment with a VEGF-A/VEGF-C cocktail. Here, we provide evidence that mouse and human myeloid-monocytic cells can undergo similar pro-lymphatic reprogramming upon activation of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…We selected pdpn as a candidate. Indeed, this interaction molecule is expressed by human monocytes and RA synoviocytes . Furthermore, pdpn is expressed in hyperproliferative psoriatic epidermis , but its contribution to disease remains to be clarified further.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the suppressive mechanism of lymphangiogenesis by platelets involves the interaction of podoplanin with CLEC-2 was not afforded. In contrast, Hur and coworkers [125] found that interaction of platelets with podoplanin-positive monocytes triggers lymphangiogenesis through activation of the podoplanin–CLEC-2 axis. The binding of CLEC-2 to the glycoprotein activates extracellular signal-regulated kinase (ERK) and AKT signaling pathways that induce transdifferentiation of monocytes to LECs and secretion of lymphangiogenic cytokines.…”
Section: Podoplanin In Inflammatory Lymphangiogenesismentioning
confidence: 94%